Conscious Awareness-Based Breathing Method on Perceived Stress, Salivary Cortisol Level and Alcohol Craving - Güneş Schareck; Sedat Çapar; Wolfgang Schareck (Addicta: The Turkish Journal on Addictions)
Alcohol abuse has emerged as a significant contributor to mortality rates in recent years. In the literature, it implies that individuals feeling under a lot of stress tend to consume more alcohol, and that stress can set off cravings during the treatment period of alcohol use disorder, leading to relapse and having a detrimental impact on the treatment. This study aims to introduce and evaluate a mindfulness-based breathing method to facilitate stress management and bolster the treatment of alcohol use disorder. The study was designed to examine patients who were admitted to an Alcohol and Substance Addiction Treatment Center for treat- ment of alcohol use disorder. These individuals were free from any mental or chronic illnesses and had abstained from drug use for the preceding 3 months. As part of the pre-test/post-test, the perceived stress scale and the Penn alcohol craving scale were administered to the experimental and control groups, and the cortisol levels in the saliva samples were assessed. Results indicate that the mindfulness-based breathing method exhibits favorable and statistically significant effects on perceived stress, salivary cortisol levels, and alcohol craving. This suggests its potential utility as a supportive intervention in alcohol treatment centers.